2001
DOI: 10.1104/pp.127.4.1728
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Purification, and Characterization of a Thermally Stable Lipase from Rice Bran. A New Member of the (Phospho) Lipase Family

Abstract: A thermally stable lipase (EC 3.1.1.3.) was first identified in rice (Oryza sativa) bran, and the enzyme was purified to homogeneity using octyl-Sepharose chromatography. The enzyme was purified to 7.6-fold with the final specific activity of 0.38 mol min Ϫ1 mg Ϫ1 at 80°C using [9, H]triolein as a substrate. The purified enzyme was found to be a glycoprotein of 9.4 kD. Enzyme showed a maximum activity at 80°C and at pH 11.0. The protein was biologically active and retained most of its secondary structure even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 10 publications
0
14
0
2
Order By: Relevance
“…In earlier work on ester formation in bread wheat (Ahmad et al, 2013) we demonstrated that the constituent involved in esterification is very thermostable. In this context, it is worth noting that a thermostable (phospho) lipase has been reported to be present in rice bran (Bhardwaj et al, 2001). The marker Xgwm295, which co-segregates with Lute, has previously been assigned to a wheat BAC (TaBAC470M18), which was in turn anchored to a position on rice chromosome 6 (Bossolini et al, 2006) based on similarity of sequences within the BAC to the gene LOC_Os06g05000 on rice chromosome 6.…”
Section: Lutein Esters In Haruhikari//sunco/indis82 Doubled Haploid mentioning
confidence: 99%
“…In earlier work on ester formation in bread wheat (Ahmad et al, 2013) we demonstrated that the constituent involved in esterification is very thermostable. In this context, it is worth noting that a thermostable (phospho) lipase has been reported to be present in rice bran (Bhardwaj et al, 2001). The marker Xgwm295, which co-segregates with Lute, has previously been assigned to a wheat BAC (TaBAC470M18), which was in turn anchored to a position on rice chromosome 6 (Bossolini et al, 2006) based on similarity of sequences within the BAC to the gene LOC_Os06g05000 on rice chromosome 6.…”
Section: Lutein Esters In Haruhikari//sunco/indis82 Doubled Haploid mentioning
confidence: 99%
“…SAG101 belongs to a family of 21 genes in Arabidopsis that is not yet characterized [23]. In addition to having TAG lipase activity, a protein isolated from rice bran, with a very low MW of 9.4 kDa, also displayed Ca 2þ -independent phospholipase activity [8] (Table 1).…”
Section: Triacylglycerol Lipasementioning
confidence: 99%
“…A characterization of the inhibition caused by different surfactants was carried out in lipase from rice bran, and the results differed from those obtained with Lip3F9. For rice bran lipase, a 2 mM concentration of SDS caused the greatest inhibitory at 50%, while Triton X-100 had an inhibitory effect at a low concentration of 0.5 mM and restored activity when in a higher concentration of 4 mM [21]. Together with previous studies, the results shown in the present study confirm that the effects of detergents are not homogenous for all enzymes nor are enzymes affected in the same way by all surfactants [22].…”
Section: Resultsmentioning
confidence: 99%